Valuation adjustment mechanisms and postmergers and acquisitions performance：evidence from China - Zhou, Yu (2023)
Mergers and acquisitions (M&A) are a common practice in publicly listed companies all around the world. But M&A also carries a significant amount of uncertainty. Because M&A can help listed companies achieve business development and scale expansion in a short amount of time, but it also requires a large amount of funds. It is being widely cited that the use of valuation adjustment methods (VAM) in M&A has long been thought of as a way to lower risks and VAM has grown into a vital study topic to support the healthy development of the M&A market. However, to adequately evaluate this conclusion, additional data are still necessary. This paper experimentally investigates 250 Chinese companies that are listed on the A-share market and finds that implementing the VAM helps enhance and stable post-performance of M&A. VAM stabilizes and enhance M&A post-merger performance through M&A types and payment methods indirectly. This paper also found that when using the VAM agreement, M&A with stock payment method performed best, while with cash performed worst and unrelated party M&A has better performance than that of related party M&A. These empirical findings will assist listed companies in promoting the M&A process more successfully, minimizing associated M&A risks, improving the sustainability of the M&A process, and making better use of the VAM.